Mustalahat Nasyat Al-Tabkh Wa Al-Istifadah Minha Fi Tamniyati Al- Lughati Al-‘Arabiyah Lada At-Talibat Bi Ma’had Tahfiz Al-Yusro - Leni Erliana; Muhammad Nanang Qosim (Uktub: Journal of Arabic Studies, 2021)
Terminology plays a very important role to develop the four skills needed in learning a language. Culinary world is often associated with women. The aim of this study is to try and to improve Arabic competency through culinary terms and to identify those terms. This study is a qualitative research, using library research to collect the data. The method used is descriptive method which allows the researcher to analyze the culinary terms. The first step taken was to write the meaning of the terms. The research found that the terms of culinary activities and their meanings from the Dictionary of Cooking Terms English-Arabic, can be divided into four parts; Seasoning and Vegetable vocabulary has 39 items, Fruit vacabulary has 19 items, Spices vacabulary has 22 items, and Cooking Tools have 26.this research also proved that culinary terms gave benefits for the students in improving their Arabic competency, through reading text, using theim preparing food recipes.